The Use of Generative Learning Model in Improving Students' Understanding of Mathematical Concepts of Al-Azhar 19 Islamic High School - Andri Kosiret; Fariani Hermin Indiyah; Dwi Antari Wijayanti (International Journal of Progressive Mathematics Education, 2021)
Background. Distance learning during the COVID-19 pandemic has changed the landscape of mathematics learning as a whole. One of the mathematics learning models that offer new concepts in distance learning is generative learning model. The Aim of the Research. This study will evaluate the effectiveness of the implementation of generative learning models in improving students' mathematical understanding abilities. The appropriate research method to test the effectiveness is quasi-experimental design because the class being experimented with is not changed, so that it does not have much effect on overall learning stability. The research sample used cluster random sampling technique where class X MIPA 3 was the experimental class while class X MIPA 2 was the control class. The research instrument used was a test of students' ability to understand mathematical concepts in the material of Logarithmic Equations as many as seven essay questions. Conclusion. There is an effect (high) of the generative learning model on the ability to understand students' mathematical concepts applied to the distance learning system at Al-Azhar 19 Ciracas Islamic Senior High School logarithmic equation material with a significance level of Î± = 0.05. Contribution. This study offers a new concept for the application of distance learning mathematics by implementing a generative learning model which in this study has contributed positively to student understanding. Â  Latar belakang. Pembelajaran jarak jauh selama pandemi COVID-19 telah mengubah lanskap pembelajaran matematika secara keseluruhan. Salah satu model pembelajaran matematika yang menawarkan konsep baru dalam pembelajaran jarak jauh adalah model pembelajaran generatif. Tujuan Penelitian. Penelitian ini akan mengevaluasi efektivitas penerapan model pembelajaran generatif dalam meningkatkan kemampuan pemahaman matematis siswa. Metode penelitian yang tepat untuk menguji keefektifan adalah desain eksperimen semu karena kelas yang diuji tidak mengalami perubahan, sehingga tidak banyak berpengaruh terhadap kestabilan belajar secara keseluruhan. Sampel penelitian menggunakan teknik cluster random sampling dimana kelas X MIPA 3 sebagai kelas eksperimen sedangkan kelas X MIPA 2 sebagai kelas kontrol. Instrumen penelitian yang digunakan adalah tes kemampuan pemahaman konsep matematika siswa pada materi Persamaan Logaritma sebanyak tujuh soal esai. Kesimpulan. Terdapat pengaruh (tinggi) model pembelajaran generatif terhadap kemampuan pemahaman konsep matematika siswa yang diterapkan pada sistem pembelajaran jarak jauh pada materi persamaan logaritma SMA Islam Al-Azhar 19 Ciracas dengan taraf signifikansi Î± = 0,05. Kontribusi. Penelitian ini menawarkan konsep baru penerapan pembelajaran jarak jauh matematika dengan menerapkan model pembelajaran generatif yang dalam penelitian ini memberikan kontribusi positif terhadap pemahaman siswa.